SKIMMING-SCANNING STRATEGIES AND VOCABULARY MASTERY IMPACT ON READING ENGLISH TEXTS - Atikah Atikah; Engliana Engliana (Universitas Indraprasta PGRI, 2018)
Since reading requires both grammatical knowledge of the language used in the intended text, strategies employed, and vocabulary mastery, therefore, it is important to gather information necessary to understand the connection how far reading strategies and vocabulary master can impact the students’ understanding on reading English texts with English as foreign language. This study aims to determine: the effect of reading strategies on the ability to read English procedure text, the influence of vocabulary mastery on the ability to read English procedure text, and the interactive influence of reading strategies and vocabulary mastery on the ability to read English procedure text. The method used in research is classroom experiment. The population was a group of students of State Junior High Schools in Tangerang – 899 students in total. The sample was 80 students (11% of the population). The results of the study show that 1) there was a significant effect of reading strategies on the ability to read English procedure text in junior high school students. This is evidenced by the value of Sig = 0,000 <0.05 and FH = 24.442; 2) there is a significant influence in the mastery of vocabulary on the ability to read English procedure text in junior high school students in the Tangerang Regency. This is evidenced by the value of Sig = 0,000 <0.05, and FH = 30,515. 3) There is a significant interactive effect on reading strategies and vocabulary mastery on the ability to read English procedure text in state junior high school students in Tangerang Regency. This is evidenced by the value of sig = 0.033 <0.05, and FH = 4.755Key Words: reading strategy; vocabulary mastery; reading in foreign language